2002
DOI: 10.1097/00000539-200205000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam and Remifentanil by Bolus Injection for Intensely Stimulating Procedures of Brief Duration: Experience with Awake Laryngoscopy

Abstract: The pharmacokinetic characteristics of midazolam and remifentanil administered by bolus injection may make them advantageous for providing brief, intense analgesia without prolonged respiratory depression. This application is particularly useful for awake, direct laryngoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…Outro estudo, que comparou diferentes doses em bolus de remifentanil associado ao propofol, mostrou reação à intubação traqueal em 30% dos pacientes na dose de 3 µg.kg -1 , enquanto que 4 µg.kg -1 permitiram boas condições para intubação traqueal em 95% dos pacientes 49 . Para intubação traqueal com o paciente acordado, o remifentanil foi usado numa dose em bolus de 3 µg.kg -1 associado ao midazolam (2 mg) 50 . Como agente único durante intubação com endoscópio de fibra óptica, infusão de até 0,5 µg.kg -1 .min -1 foi associada a maior conforto, mas com maior incidência de lembrança do que o uso combinado de midazolam (10 mg) e fentanil (1,5 µg.kg -1 ) por via venosa 51 .…”
Section: Intubação Traqueal Sem Bloqueador Neuromuscularunclassified
See 1 more Smart Citation
“…Outro estudo, que comparou diferentes doses em bolus de remifentanil associado ao propofol, mostrou reação à intubação traqueal em 30% dos pacientes na dose de 3 µg.kg -1 , enquanto que 4 µg.kg -1 permitiram boas condições para intubação traqueal em 95% dos pacientes 49 . Para intubação traqueal com o paciente acordado, o remifentanil foi usado numa dose em bolus de 3 µg.kg -1 associado ao midazolam (2 mg) 50 . Como agente único durante intubação com endoscópio de fibra óptica, infusão de até 0,5 µg.kg -1 .min -1 foi associada a maior conforto, mas com maior incidência de lembrança do que o uso combinado de midazolam (10 mg) e fentanil (1,5 µg.kg -1 ) por via venosa 51 .…”
Section: Intubação Traqueal Sem Bloqueador Neuromuscularunclassified
“…A different study comparing different remifentanil bolus doses associated to propofol, has shown tracheal intubation reaction in 30% of patients with 3 µg.kg -1 , while 4 µg.kg -1 has provided good tracheal intubation conditions in 95% of patients 49 . For tracheal intubation with awaken patients, remifentanil was used in bolus dose of 3 µg.kg -1 associated to midazolam (2 mg) 50 . As single agent during fiber optics endoscopic intubation, up to 0.5 µg.kg -1 .min -1 infusion was associated to better comfort, but with a higher incidence of memory as compared to combined intravenous midazolam (10 mg) and fentanyl (1.5 µg.kg -1 ) 51 .…”
Section: Tracheal Intubation Without Neuromuscular Blockermentioning
confidence: 99%
“…A single case report was published in which a remifentanil bolus was used to provide analgesia for direct laryngoscopy in a conscious patient without any topical anesthesia [13]. Advantages of using remifentanil may include rapid titration and increased patient comfort.…”
Section: Introductionmentioning
confidence: 99%
“…If there is a question regarding how successful a standard induction will be, it may be possible to perform an "awake look" using a combination of midazolam and a single bolus dose of remifentanil [23] . With this technique, the patient is positioned in the standard fashion, preoxygenated, and a dose of 1-2 μg/kg of remifentanil is given.…”
Section: In the Operating Roommentioning
confidence: 99%